PENGARUH KUALITAS LAYANAN, KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN PADA RESTORAN GREAT INDONESIA - Kurniadi, Arben; Hadibrata, Baruna (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
Great Indonesian restaurant is a restaurant located in Terminal Three Soekarno-Hatta Airport. A decline in the level of customer satisfaction resulted in a high level of canceled bills and decrease in income, based on studies of the factors that support the improvement of customer satisfaction in this restaurant is the quality of service, price and quality perception of the product. This study aims to examine and analyze the impact of service quality, price and service quality perceptions influence on customer satisfaction Great Indonesian Restaurant. Type of research is descriptive quantitative model. The population in the study for 1300 respondents and with slovin formula samples taken as many as 93 respondents, the sampling using the technique of Non-Probability Sampling with accidental sampling approach. Results of research addressing that perception variable price and service quality and significant positive effect on customer satisfaction, while the variable quality of service partially no significant influence on customer satisfaction. Simultaneously, the third independent variable is the quality of service, price and service quality perceptions significant effect on customer satisfaction in the Restaurant Great Indonesia